Characterization techniques of packing material colonization in gas biofiltration processes. Issue 1 (March 2014) - Andres, Yves; Dumont, Eric; Gerente, Claire
Abstract : Biological air treatment is largely used for the decontamination of large air streams with low pollutant concentrations. As a result of microbial metabolism, the pollutants are degraded into carbon dioxide and water or converted into cell biomass. Three main research domains have emerged within the field of biofiltration: filter bed development, process optimization, and microbiological studies (community, nutrients, …). The objective of this paper is to focus on the microbial activities in air biofiltration processes. The nutrient contribution and the packing material effects are described. Special attention is paid to the description of techniques for the characterization and identification of the microbial population.